The Influence of AI-Based Shopping Experience on Consumer Value through Cognition and Attitude - I Putu Putra Astawa; I Gusti Ayu Lia Yasmita; I Komang Trisna Eka Putra (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2025)
Rapid advances in artificial intelligence (AI) have transformed online retail, yet many studies still empha-sise technical performance rather than the psychological mechanisms through which AI-driven experi-ences shape consumer value. This gap is evident in emerging markets such as Indonesia, where enthuse-asm for AI coexists with persistent concerns about data transparency and system reliability. Addressing this issue, the present study examines how AI-based shopping experiences influence consumer value by incorporating two mediating variables: AI Cognition, consumers’ understanding, Cognitive Load, Deci-sion Making, and Cognitive Bias in AI, and Attitude toward AI, which reflects their emotional and evalua-tive responses. A quantitative survey involving 150 active e-commerce users who had interacted with AI features (recommendation systems, chatbots, and personalisation tools) was analysed using SEM–PLS. The findings show that AI-based shopping experiences significantly enhance consumer value, both di-rectly and indirectly. Among the mediators, Attitude toward AI emerged as the dominant pathway, indi-cating that emotional acceptance plays a more influential role than cognitive appraisal in translating AI-driven experiences into perceived value. These results highlight that strengthening users’ emotional comfort and positive evaluations of AI is essential for maximising value creation, offering important im-plications for both theory and the design of consumer-centred AI systems.